Pemberdayaan Masyarakat Melalui Edukasi Partisipatif PMT Balita Berbasis Pangan Lokal di Kecamatan Wates Kabupaten Kediri - Miladitiya, Aulia; Rizky Alfiqi Nuriza; Purwanti Nurfita Sari; Ulfie Rahmah Aliyah (Health Community Engagement, 2025)
Abstract: Nutritional problems in toddlers, particularly stunting, remain a serious challenge in the development of human resources in Indonesia. One effective strategy to address this issue is the provision of Supplementary Feeding (PMT) based on local food sources. This community service activity was carried out in Wates Subdistrict, Kediri Regency, with the aim of improving the knowledge, attitudes, and practices of mothers of toddlers, posyandu cadres, and health workers in preparing nutritious, hygienic, and appealing PMT using local food ingredients. The method used was an educational and participatory approach through education and evaluation using pre-test and post-test to measure changes in participants' knowledge. The results showed a significant increase in participants' knowledge levels after the counseling session, with the number of participants in the high knowledge category rising from 14 to 20 individuals. This indicates that nutrition education based on local food is effective in enhancing community understanding of providing healthy food for toddlers. Therefore, this program can serve as a strategic effort to reduce stunting rates and promote sustainable food and nutrition self-sufficiency in families. Keywords: Stunting, nutrition education, supplementary feeding, local food Abstrak: Masalah gizi pada balita, khususnya stunting, masih menjadi tantangan serius dalam pembangunan sumber daya manusia di Indonesia. Salah satu strategi yang dinilai efektif untuk mengatasi masalah ini adalah melalui Pemberian Makanan Tambahan (PMT) berbasis pangan lokal. Kegiatan pengabdian masyarakat ini dilaksanakan di Kecamatan Wates, Kabupaten Kediri, dengan tujuan meningkatkan pengetahuan, sikap, dan praktik ibu balita, kader posyandu, dan tenaga kesehatan dalam mengolah PMT berbahan dasar pangan lokal yang bergizi, higienis, dan menarik bagi balita. Metode yang digunakan adalah pendekatan edukatif dan partisipatif melalui penyuluhan, serta evaluasi pre-test dan post-test untuk mengukur perubahan pengetahuan peserta. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada tingkat pengetahuan peserta setelah mengikuti penyuluhan, dengan peningkatan jumlah peserta dalam kategori pengetahuan tinggi dari 14 menjadi 20 orang. Hal ini menunjukkan bahwa penyuluhan gizi berbasis pangan lokal efektif dalam meningkatkan pemahaman masyarakat mengenai penyediaan makanan sehat bagi balita. Dengan demikian, program ini dapat menjadi salah satu upaya yang strategis dalam menurunkan angka stunting serta mewujudkan kemandirian pangan dan gizi keluarga secara berkelanjutan. Kata kunci: Stunting, edukasi gizi, PMT, pangan lokal